2017
DOI: 10.1111/1758-2229.12570
|View full text |Cite
|
Sign up to set email alerts
|

Methanotroph‐derived bacteriohopanepolyol signatures as a function of temperature related growth, survival, cell death and preservation in the geological record

Abstract: Interpretation of bacteriohopanepolyol (BHP) biomarkers tracing microbiological processes in modern and ancient sediments relies on understanding environmental controls of production and preservation. BHPs from methanotrophs (35-aminoBHPs) were studied in methane-amended aerobic river-sediment incubations at different temperatures. It was found that: (i) With increasing temperature (4°C-40°C) a 10-fold increase in aminopentol (associated with Crenothrix and Methylobacter spp. growth) occurred with only margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The three strains exhibited similar hopanol distributions to each other (see Table 3 for data for the individual strains), although to a lesser degree than with the FAs. Tetra, penta and hexafunctionalised BHPs, from which the hopanols analyzed in this studied are derived, have been described across a range of methanotrophs, including from the genera Methylomarinum , Methylomarinovum , Methylomicrobium , (Rush et al, 2016), Methylomonas , Methylosinus , Methylocella , Methylacidiphilium (van Winden et al, 2012b), Methylobacter (Osborne et al, 2017) as well as in a Methylovulum -like strain M200 (van Winden et al, 2012b). Unsaturated aminotriol and aminotetrol BHPs have only to date been described in a Methylovulum -like strain M200 (van Winden et al, 2012b) which suggests that they are characteristic of the Methylovulum genera.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three strains exhibited similar hopanol distributions to each other (see Table 3 for data for the individual strains), although to a lesser degree than with the FAs. Tetra, penta and hexafunctionalised BHPs, from which the hopanols analyzed in this studied are derived, have been described across a range of methanotrophs, including from the genera Methylomarinum , Methylomarinovum , Methylomicrobium , (Rush et al, 2016), Methylomonas , Methylosinus , Methylocella , Methylacidiphilium (van Winden et al, 2012b), Methylobacter (Osborne et al, 2017) as well as in a Methylovulum -like strain M200 (van Winden et al, 2012b). Unsaturated aminotriol and aminotetrol BHPs have only to date been described in a Methylovulum -like strain M200 (van Winden et al, 2012b) which suggests that they are characteristic of the Methylovulum genera.…”
Section: Resultsmentioning
confidence: 99%
“…β-hydroxy FAs have been detected in a range of methanotrophic bacteria (Bowman et al, 1991) and their source has been identified as the lipid A component of lipopolysaccharides (Wollenweber and Rietschel, 1990), which are a major constituent of the outer membrane of Gram-negative bacteria (Keinänen et al, 2003; Wollenweber and Rietschel, 1990). Methanotrophs also produce bacteriohopanepolyols (BHPs) which can be tetra, penta or hexafunctionalised (Cvejic et al, 2000a; van Winden et al, 2012b; Rush et al, 2016; Osborne et al, 2017). BHPs have been identified with a range of modifications including 3β-methylation and unsaturations at the Δ 6 and Δ 11 positions (Talbot et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the abundance of BHT II produced by any one organism may also vary with environmental conditions. BHPs may be regulated in response to particular environmental conditions, such as temperature (Kulkarni, Wu, & Newman, ; Osborne et al., ), pH (Garby et al., ; Kulkarni et al., ), and nutrient concentrations (Doughty, Hunter, Summons, & Newman, ). It is possible that environmental conditions present in marine OMZ systems may prompt the production of high abundances of BHT II while conditions in Lake Fryxell do not.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the abundance of BHT II produced by any one organism may also vary with environmental conditions. BHPs Lake Fryxell may be regulated in response to particular environmental conditions, such as temperature (Kulkarni, Wu, & Newman, 2013;Osborne et al, 2017), pH (Garby et al, 2017;Kulkarni et al, 2013), and nutrient concentrations (Doughty, Hunter, Summons, & Newman, 2009).…”
Section: Majorsmentioning
confidence: 99%